The distribution, phenology, host range and pathogen prevalence of Ixodes ricinus in France: a systematic map and narrative review - Perez, Grégoire; Bournez, Laure; Boulanger, Nathalie; Fite, Johanna; Livoreil, Barbara; McCoy, Karen D.; Quillery, Elsa; René-Martellet, Magalie; Bonnet, Sarah I. (Peer Community Journal)

(untitled)
The tick Ixodes ricinus is the most important vector species of infectious diseases in European France. Understanding its distribution, phenology, and host species use, along with the distribution and prevalence of associated pathogens at a national scale is essential for developing prevention strategies. The aim of this paper is to provide a systematic map and narrative review of the existing knowledge on the eco-epidemiology of I. ricinus in France. Using literature published up to 2020, the present paper provides a distribution map for the species and a summary of environmental factors explaining observed geographical differences in phenology and temporal differences in abundance. The diversity of vertebrate host species used by this tick, along with their degree of infestation when available, are presented and discussed with respect to their potential contribution to the population dynamics of I. ricinus and the circulation of tick-borne zoonotic pathogens. Prevalence data of detected pathogens are summarised in different maps. Results from 187 identified references show that the species is present in most departments, but scarce under Mediterranean climates and in coastal habitats. Its phenology is generally bimodal with climate-associated variations. Abundance seems positively influenced by forest cover and host abundance. Rodents and ruminants are the most studied species groups, but the diversity of sampling protocols (e.g., location, season, exhaustivity of inspection) precluded direct comparisons between groups. Data on pathogens are patchy, with most studies conducted near research laboratories. Among pathogens, Borrelia burgdorferi sensu lato is the most examined and seems most prevalent in north-eastern and central France. The review highlights the gaps in our knowledge of tick-host-pathogen interactions, their ecologies and their distributions, and demonstrates the need to address these gaps in order to optimize tick and tick-borne diseases prevention and control.